Optimization for achieving sustainability in low code development platform - Phalake, Vaishali S; Joshi, Shashank D; Rade, Kuldip A; Phalke, Vijay S; Molawade, Mayuri (International journal on interactive design and manufacturing, 2024)
The Low Code Development Platform (LCDP) is a versatile platform to handle process, database, mobile and web based applications. The platform provides us opportunity to digitize the activities in IT, telecommunication, government and all other industries as well as different departments of the organization in the form of applications. The manufacturing industry can also incorporate low-code apps for data analysis and their manufacturing processes to automate the process. This research work has proposed a novel sustainable LCDP with optimization techniques for data analysis. The proposed platform allows user to execute data analysis applications in optimization and without optimization mode. The result shows that optimized LCDP reduces both space and time required for the any type of application.